POST-EARTHQUAKE CRUSH SYNDROME FROM A DISASTER NURSE PERSPECTIVE: A CASE REPORT: A CASE OF CRUSH SYNDROME - HELLAÇ, Muhammet; YILDIRIM, NİLÜFER; GÖRDES AYDOĞDU, Nihal (Göbeklitepe Medical Science Journal, 2024)
There are some medical conditions that nurses should be aware of during earthquake disasters. Crush Syndrome can be seen due to staying in certain positions for a long time under earthquake debris. The reperfusion, which starts immediately after the rescue of the earthquake victim, causes the contents, which are released after muscle cell destruction and have toxic effects on other organs, to pass into the systemic circulation. This is a serious condition that affects the body system. As a result, cardiopulmonary failure, diffuse edema, hyperkalemia, hyperphosphatemia, acidosis, coagulopathy, infections, and most importantly acute renal failure may develop and the patient may die. Medical treatment and nursing care to be applied are important. In this case report, information about a patient with crush syndrome who developed after an earthquake and an example of a nursing care plan is given. At the end of the health service he received, the patient was healed, his kidney functions improved, and his wounds became quite good. It has been concluded that it is very important for nurses to increase their knowledge about Crush Syndrome that can develop in disasters, to improve themselves, and to take part in every stage of disaster and crisis management with individual and social awareness.